On the Robustness of Social Norm Elicitation - Christian König-Kersting (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
We study the robustness of Krupka and Weber's method (2013) for eliciting social norms. In two experiments with more than 1200 participants, we find that participants' response patterns are invariant to differences in the salience of the monetarily incentivized coordination aspect. We further demonstrate that asking participants for their personal first and second order beliefs without monetary incentives results in qualitatively identical responses. In addition, we observe that participants give sensible responses whether or not they understand the task or their monetary incentives. Overall, Krupka and Weber's method produces remarkably robust response patterns.
Keywords: C72; C90; D90; 330; social norms; incentives; beliefs; task comprehension; robustness